Joint Functional Focus of Models of Civil Liability for Damage Inflicted on Patients - Prymak, Volodymyr; Koreniuk, Olga; Poharchenko, Tatiana (International Journal of Criminology and Sociology, 2021)
One of the key areas of legal regulation of any aspect of public life (especially when it comes to personal moral rights inalienable from a person, including those that ensure the person's physical existence and reflect the human dignity inherent in every individual) is the establishment of legal guarantees for the observance and protection of subjective rights belonging to a person. The purpose of this study is to determine the centripetal (in value and functional terms) trends in the development and application of similar legal models and means of legal regulation of relations arising from harm inflicted on patients. It was concluded on the inevitability of the intensification of the world, and European, in particular, tendencies regarding the diverse use by national legal systems of similar functional legal instruments for compensation for property and moral damage in order to ensure effective protection of personal non-property and property rights of patients and related persons. Therewith, the identity of a certain national legal mechanism will be determined mainly by the orientation of the legal policy of a particular state towards the top-priority implementation of certain characteristics of compensation and proactive, preventive (which, in the context under consideration, appears as a guarantee for the observance of the rights of patients and the performance of obligations by the providers of medical services) functions of civil liability.